When Pain Brings Gain: Soccer Players Behavior and Admissions Suggest Feigning Injury to Maintain a Favorable Scoreline - Derbyshire, Stuart W. G.; Angel, Ilana; Bushell, Richard (Frontiers in Psychology, 2016)
The rules of soccer dictate that play, once halted, cannot continue if a player is injured. Players may take advantage of this rule by feigning injury to preserve beneficial match positions. Thirty Euro 2008 matches, 90 Premier League matches and 63 World Cup 2010 matches were reviewed for the timing and severity of injuries. The number of injuries was compared between teams that benefited from stopping the game and those that did not benefit. The number of low-level injuries, not resulting in substitution or subsequent problems, was directly compared for benefit and non-benefit teams for each 15-minute period following kick off. Statistical significance was assessed using appropriate non-parametric tests. In addition, seven current players and three managers were interviewed and were asked about feigning injury. Teams that benefited from game stoppages suffered significantly more minor injuries in the last 15 minutes of matches compared with those that did not benefit. Four of the players directly admitted feigning injury. When it is beneficial, soccer players can and do successfully feign injury to stop the game. Consequently it is possible that others might also successfully feign injury, pain or disease when motivated to do so.